Physiological and Transcriptomic Comparison of Two Sunflower (Helianthus annuus L.) Cultivars With High/Low Cadmium Accumulation - Fu, Yuanzhi; Zhatova, Halyna; Li, Yuqing; Liu, Qiao; Trotsenko, Volodymyr; Li, Chengqi (Frontiers in Plant Science, 2022)
The toxic heavy metal cadmium (Cd) is easily absorbed and accumulated in crops and affects human health through the food chains. Sunflower (Helianthus annuus L.) is a globally important oil crop. In this study, two sunflower cultivars, 62\3 (high Cd) and JB231AC (low Cd), were chosen to compare physiological and transcriptomic responses at different Cd concentrations (0, 25, 50, 100 μM). The results showed that JB231AC had better Cd tolerance than 62\3. The contents of H2O2 and MDA (malondialdehyde) in 62\3 were lower than that in JB231AC under Cd stress, but the activities of SOD (superoxide dismutase) and POD (peroxidase) in JB231AC were higher than in 62\3, which indicated that JB231AC had a strong ability to remove reactive oxygen species (ROS)-induced toxic substances. Many deferentially expressed ABC (ATP-binding cassette) and ZIP (Zn-regulated transporter, Iron-regulated transporter-like protein) genes indicated that the two gene families might play important roles in different levels of Cd accumulation in the two cultivars. One up-regulated NRAMP (Natural resistance-associated macrophage protein) gene was identified and had a higher expression level in 62\3. These results provide valuable information to further understand the mechanism of Cd accumulation and provide insights into breeding new low Cd sunflower cultivars.